Quantitative Evaluation of the Inferential Statistics Integration Skills in Practical Research of Grade 12 Students: As a Basis for a Remediation Program - Morata, Jan Angelo; Poblete, John Paolo (Journal of Interdisciplinary Perspectives, 2024)
This study evaluated students' perceived versus actual integration skills in statistics on seven central topics of the course concerning so-called 'inferential statistics,' namely: t-tests (independent and dependent), Analysis of Variance (ANOVA), Chi-square tests, Pearson Product Moment correlation coefficient, Spearman rank correlation coefficient and regression analysis. Descriptive statistics indicated that students perceived their skills as developing (mean = 1.62), but their actual performance was lower, categorized as beginning (mean = 1.38). Students performed weakest on Chi-square tests (mean = 1.10) and ANOVA (mean = 1.30). However, correlation analysis showed that most topics had no significant relationship between perceived performance and actual performance (p = 0.045), except for the Pearson Product Moment correlation coefficient, which had a moderate positive correlation (ρ = 0.260). Despite this, the actual performances for all topics were still low. Thus, the findings show a gap between perceived and actual skills. These results indicate that a comprehensive remediation program will include all seven inferential statistics topics utilized in this study. The course of study in this regard should be designed to enhance conceptual understanding, practical competency, and the student's capacity for appropriate self-assessment. A structured approach that matches focused workshops with practical work and individual support will help ensure that students develop both the theoretical and practical competence they need to do the statistical analysis, and that is through targeted instructional workshops and interactive statistical software training as the remediation program.